Sound Transmission Loss of a Panel Backed by a Small Enclosure. Issue 4 (December 2015) - Ruber, Karel; Kanapathipillai, Sangarapillai; Randall, Robert
Sound transmission loss (STL) tests of acoustic insulation panels are commonly performed in large reverberation rooms. Large size rooms are required by acoustic standards to ensure that a large number of modes can be excited in the frequency range of interest, to create a diffuse sound field. However for STL measurements in low frequency range small enclosures should be able to provide adequate homogenous sound fields, namely 'pressure sound fields'. The expected effect of the air sealed in an enclosure backing a panel, is to increase the stiffness of the panel artificially raising the first natural frequency of the panel, which corresponds to a minimum value in the STL spectrum. In this paper the influence of the air cavity's added stiffness on the panel STL is investigated in detail. As expected the effect of the sealed air is to increase the plate stiffness and as a result to increase the frequency of its first natural mode, however the effect on the STL in this frequency region is unexpectedly insignificant which removes the need for correcting STL measurements using small enclosures in low frequency range-around their first natural frequency of the panels.